TINDAK ILOKUSI DALAM PERCAKAPAN BAHASA INDONESIA PADA ANAK USIA 4;0-5;0: illocutionary act, conversation, age of 4;0–5;0 years old - Ira Eko Retnossari (Universitas PGRI Adi Buana, 2011)
Speech act is the sentence production in certain condition and the smallest unit of language communication. One of the speech acts is illocutionary acts. This research is aimed to identify the types of illocutionary act in Indonesian conversation.The approach of this research is the descriptive qualitative approach. The data of research is the conversation that describes the types of illocutionary act. To get this data, the techniques used are observation, planned interview, stimulating technique, recording technique, and noting technique:Fhis result of this research shows that the child has mastered three types of illocutionary act. They are (1) assertive or representative, (2) directive, and (3) expressive. First, examples of assertive type are the informative statement, agreement, conclusion, and refusing statement. Secondly, the examples of directive type are asking information, suggesting, ordering, and requesting. Last, the examples of expressive type are apologizing and congratulating statement.